Mapping Thermoelectric Transport in a Multicomponent Alloy Space. (22nd June 2022) - Gurunathan, Ramya; Sarker, Suchismita; Borg, Christopher K. H.; Saal, James; Ward, Logan; Mehta, Apurva; Snyder, G. Jeffrey
Abstract: Interest in high entropy alloy thermoelectric materials is predicated on achieving ultralow lattice thermal conductivity κL through large compositional disorder. However, here it is shown that for a given mechanism, such as mass contrast phonon scattering, κL will be minimized along the binary alloy with highest mass contrast, such that adding an intermediate mass atom to increase atomic disorder can increase thermal conductivity. Only when each component adds an independent scattering mechanism (such as adding strain fluctuation to an existing mass fluctuation) is there a benefit. In addition, both charge carriers and heat‐carrying phonons are known to experience scattering due to alloying effects, leading to a trade‐off in thermoelectric performance. Analytic transport models are applied, based on perturbation and effective medium theories, to predict how alloy scattering will affect the thermal and electronic transport across the full compositional range of several pseudo‐ternary and pseudo‐quaternary alloy systems. To do so, a multicomponent extension is demonstrated to both thermal and electronic binary alloy scattering models based on the virtual crystal approximation. Finally, it is shown that common functional forms used in computational thermodynamics can be applied to this problem to further generalize the scattering behavior that is modeled. Abstract : A multicomponent alloy extension to thermal and electronic analytic transport models is presented by drawing analogy to computational thermodynamics formalisms. The model is applied to map out the transport properties across the full compositional range of several pseudo‐ternary and pseudo‐quaternary thermoelectric alloy systems. Finally, design rules for achieving a thermal conductivity reduction through multicomponent alloying are presented.